Effects of exercise interventions on bone health and body composition in postmenopausal women with breast cancer: a systematic review and meta-analysis - Yu, Shan; Gao, Chengfei; Yi, Chuanjian; Hei, Jingyou (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the effects of exercise interventions on bone health and body composition in postmenopausal women with breast cancer.MethodsA systematic search was conducted across PubMed, EMBASE, Web of Science, CENTRAL, and CNKI databases for randomized controlled trials (RCTs) published before October 2024. Data from eligible studies were extracted and analyzed using STATA software.ResultsEight RCTs comprising 1099 participants were included. The results indicated no significant differences between exercise and control interventions in patients’ bone mineral density (BMD) at the lumbar spine (WMD = 0.116, 95% CI [-0.357, 0.589], p = 0.631), femoral neck (WMD = -0.214, 95% CI [-0.497, 0.068], p = 0.137), or total hip (WMD = 0.299, 95% CI [-0.283, 0.882], p = 0.314). For body composition parameters, exercise interventions led to significant improvements in lean mass (WMD = 0.192, 95% CI [0.023, 0.362], p = 0.026) and marked reductions in percent body fat (WMD = -1.327, 95% CI [-2.587, -0.066], p = 0.039) compared to the control. However, no significant differences were observed in body weight (WMD = -0.024, 95% CI [-0.193, 0.146], p = 0.784) or fat mass (WMD = -0.078, 95% CI [-0.703, 0.546], p = 0.806) between the two interventions.ConclusionThe current evidence suggested that exercise interventions effectively improve lean mass and reduce percent body fat but have a limited impact on BMD in postmenopausal women with breast cancer. A multimodal, individualized exercise program is recommended to address the challenges of bone health and body composition in this population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024613744.